Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G.; Galotta, G.; Cancellieri, L.; Savo, V. (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Nitrogen deposition in Mediterranean forests. - Roda, F.; Avila, a; Rodrigo, A. (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
The following values have no corresponding Zotero field: accession-num: 11939283
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N.; Pemonge, M.-H. H.; Ouassou, A.; Sbay, H.; Kremer, A.; Petit, R. J. (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11555243
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R.; Perotto, S.; Girlanda, M.; Vidano, G.; Luppi, a M. (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11050558
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Phenological and growth patterns of the Mediterranean oak Quercus suber L. - Oliveira, Graca; Correia, Otflia (Trees-Structure and …, 1994)
The phenology of Quercus suber L., a dominant species of the montados in the Iberian Peninsula, was studied for 2 years in southwest Portugal. The seasonal progression of phenological events was analyzed in seven trees. Selected branches were examined monthly for shoot elongation, leaf number, branching, flowering, and fruiting. Radial stem growth and specific leaf weight were also studied. Active growth was observed from early spring to early summer. Reserves accumulated during winter and high photosynthetic activity in early spring apparently supported this strong development. The growth flush started with stem radial increment, which seemed to be impaired by spring rainfall. Male inflorescence production was the next phenological event. Old leaves were shed during new twig and leaf emergence. Shoot elongation and the number of new leaves produced were well correlated with the previous-year shoot's length, and were not clearly related to climatic factors. Radial growth resumed in au- tumn at a lower rate than in the previous spring, a possible consequence of a reserve depletion due to lower photo- synthetic production in summer and investment on fruit maturation, which was complete by late autumn. Premature and excessive new leaf production were apparently sub- jected to self-pruning strategies related to the development of each tree's crown. Younger cork-oaks produced shorter and fewer shoots per module, and more sclerophyllous leaves than the older ones. A high intra-specific variability was observed in all the results.
Keywords: Growth; Phenology; Quercus suber; specific leaf weight; Trees

Photosynthetic acclimation in trees to rising atmospheric CO2: a broader perspective - Gunderson, C. A.; Wullschleger, S. D. (Photosynthesis Research, 1994)
Analysis of leaf-level photosynthetic responses of 39 tree species grown in elevated concentrations of atmospheric CO 2 indicated an average photosynthetic enhancement of 44% when measured at the growth [CO2]. When photosynthesis was measured at a common ambient [CO2], photosynthesis of plants grown at elevated [CO2] was reduced, on average, 21% relative to ambient-grown trees, but variability was high. The evidence linking photosynthetic acclimation in trees with changes at the biochemical level is examined, along with anatomical and morphological changes in trees that impact leaf- and canopy-level photosynthetic response to CO 2 enrichment. Nutrient limitations and variations in sink strength appear to influence photosynthetic acclimation, but the evidence in trees for one predominant factor controlling acclimation is lacking. Regardless of the mechanisms that underlie photosynthetic acclimation, it is doubtful that this response will be complete. A new focus on adjustments to rising [COz] at canopy, stand, and forest scales is needed to predict ecosystem response to a changing environment.
The following values have no corresponding Zotero field: accession-num: 24311130
Keywords: elevated atmospheric CO 2; global carbon cycle; photosynthetic acclimation; Trees